(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article analyzes modern and effective agrotechnical methods of almond cultivation in arid and water-scarce areas. During the research, the issues of maintaining soil moisture, introducing drip irrigation systems and choosing drought-resistant varieties were studied. Also, scientific conclusions are given on the effect of shaping and fertilizing trees on productivity.